EKSISTENSI HAK MENDAHULUI NEGARA ATAS HUTANG PAJAK DEBITOR DALAM PROSES KEPAILITAN - Muhammad Adhiluhung Sosiawan (CV Putra Publisher, 2022)
The pre-emptive rights owned by the state for tax claims on the goods belonging to the Tax Bearer are regulated in Article 21 of Law Number 16 of 2009 concerning General Provisions and Tax Procedures (UU KUP), but legal certainty has not been realized due to several bankruptcy cases. Pre-emptive rights have not yet been implemented. The purpose of this study is to understand and analyze the existence of the State's prior rights over debtors' tax debts in the bankruptcy process, and to understand and analyze efforts to realize legal certainty over the State's prior rights related to debtor's tax debt obligations in the bankruptcy process. The legal theory used as the basis for thinking in this research is the theory of legal certainty and the theory of state precedence. The method used in this study is a normative juridical research method. The data used is secondary data, the legal materials used in this study are derived from the results of library research in the form of primary legal materials, secondary legal materials. For the analysis of legal materials, systematic interpretation and grammatical interpretation are used. The results of the study show that the position of the state's prior rights in Article 21 of the KUP Law does not provide legal certainty. Legal certainty of the state's pre-emptive rights on tax payables can be realized by objecting to or rejecting the list of receivables by making a request for a procedure review at the time of verification or verification of the debtor's debt, or can apply for a procedure review to the Commercial Court at the District Court, and can also make cassation action if the application for procedure review is rejected at the Commercial Court level.